1987
DOI: 10.1093/cvr/21.9.678
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive assessment of the age related changes in stiffness of major branches of the human arteries

Abstract: The static mechanical properties of major branches of the human arteries (common carotid artery, abdominal aorta, femoral artery, and brachial artery) were studied in 39 subjects, aged 6-81 years, using an ultrasonic phase locked echo tracking system that allows continuous transcutaneous measurement of the diameter of the artery. The stiffness indices were calculated from the relation between systemic blood pressure and arterial diameter. With advancing age there was a significant increase in the diameter of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
351
4
7

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 613 publications
(388 citation statements)
references
References 0 publications
20
351
4
7
Order By: Relevance
“…where ln is the natural logarithm, Ps is systolic and Pd is diastolic blood pressures in mmHg, Dd is diastolic aortic diameter and Ds is systolic aortic diameter 16 . Results are based on mean β stiffness index from three assessments.…”
Section: Methodsmentioning
confidence: 99%
“…where ln is the natural logarithm, Ps is systolic and Pd is diastolic blood pressures in mmHg, Dd is diastolic aortic diameter and Ds is systolic aortic diameter 16 . Results are based on mean β stiffness index from three assessments.…”
Section: Methodsmentioning
confidence: 99%
“…Elastic modulus, distensibility, and stiffness index β are the methods used for a local assessment of arterial stiffness 33, 34. However, validity and reproducibility of these methods are limited because of their dependence on the patient's blood pressure 7, 9.…”
Section: Discussionmentioning
confidence: 99%
“…These indices are equations that rely on static data, such as end-systolic and end-diastolic diameter or systolic and diastolic blood pressure. 23,24 They result in a single indexed value for compliance, whereas our method can evaluate compliance continuously over time. These indices are also unable to isolate and quantify the individual contributions of radial and longitudinal motion to aortic compliance.…”
Section: Discussionmentioning
confidence: 99%
“…This functioned as control for differences in patients' blood pressure at the time of TEE image acquisition, minimizing its impact as a confounding variable when measuring compliance. Previous work has suggested that aortic pressure may contribute less than changes in volume with regard to indices of aortic compliance 23 ; therefore, the impact of lacking simultaneous invasive pressure measurements should be minimal.…”
Section: Diabetes Mellitus 19 Dyslipidemia 50mentioning
confidence: 99%